2002
DOI: 10.1016/s1010-7940(02)00529-8
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary blastoma: report of five cases and identification of clinical features suggestive of the disease

Abstract: Compared to operated NSCLC, PB are rare, large, and symptomatic tumors; they affect younger patients and carry a worse prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
50
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 17 publications
1
50
0
4
Order By: Relevance
“…The treatment of choice has been surgical excision, radiation and, in selected cases, a combination of chemotherapy with radiation (19). Adjunctive therapy is still controversial because of lack of data.…”
Section: █ Discussionmentioning
confidence: 99%
“…The treatment of choice has been surgical excision, radiation and, in selected cases, a combination of chemotherapy with radiation (19). Adjunctive therapy is still controversial because of lack of data.…”
Section: █ Discussionmentioning
confidence: 99%
“…On CT, pulmonary blastoma is seen as a mixed solid and cystic lesion with variable contrast enhancement and a necrotic centre. The tumor is usually limited to one lung, with all pulmonary lobes equally affected [5]. In their series, Van Loo et al [6], found an upper lobe predominance, with 27 tumors located in the upper lobes, while 19 tumors were located in the lower lobes and 1 in the middle lobe.…”
Section: Discussionmentioning
confidence: 95%
“…Plevra sıvısı alışılmadık şekilde görülebilirse de ortak belirtileri öksürük, hemoptizi ve göğüs ağrısıdır. Pulmoner blastoma çoğunluğu erişkin ve genç kadınlarda bildirilmiştir (9). Olgumuz ise 3 yaşında olup öksürük ve nefes darlığı şikâyetleri mevcuttu.…”
Section: Discussionunclassified